Downregulation of ARID1B, a tumor suppressor in the WNT subgroup medulloblastoma, activates multiple oncogenic signaling pathways. Issue 18 (5th May 2021) - Deogharkar, Akash; Singh, Satishkumar Vishram; Bharambe, Harish Shrikrishna; Paul, Raikamal; Moiyadi, Aliasgar; Goel, Atul; Shetty, Prakash; Sridhar, Epari; Gupta, Tejpal; Jalali, Rakesh; Goel, Naina; Gadewal, Nikhil; et al.
Abstract: Medulloblastoma, a common pediatric malignant brain tumor, consists of four distinct molecular subgroups WNT, SHH, Group 3 and Group 4. Exome sequencing of 11 WNT subgroup medulloblastomas from an Indian cohort identified mutations in several chromatin modifier genes, including genes of the mammalian SWI/SNF complex. The genome of WNT subgroup tumors is known to be stable except for monosomy 6. Two tumors, having monosomy 6, carried a loss of function mutation in the ARID1B gene located on chromosome 6. ARID1B expression is also lower in the WNT subgroup tumors compared to other subgroups and normal cerebellar tissues that could result in haploinsufficiency. The short hairpin RNA-mediated knockdown of ARID1B expression resulted in a significant increase in the malignant potential of medulloblastoma cells. Transcriptome sequencing identified upregulation of several genes encoding cell adhesion proteins, matrix metalloproteases indicating the epithelial–mesenchymal transition. The ARID1B knockdown also upregulated ERK1/ERK2 and PI3K/AKT signaling with a decrease in the expression of several negative regulators of these pathways. The expression of negative regulators of the WNT signaling like TLE1, MDFI, GPX3, ALX4, DLC1, MEST decreased upon ARID1B knockdown resulting in the activation of the canonical WNT signaling pathway. Synthetic lethality has been reported between SWI/SNF complex mutations and EZH2 inhibition, suggesting EZH2 inhibition as a possible therapeutic modality for WNT subgroup medulloblastomas. Thus, the identification of ARID1B as a tumor suppressor and its downregulation resulting in the activation of multiple signaling pathways opens up opportunities for novel therapeutic modalities for the treatment of WNT subgroup medulloblastoma.